ATTITUDES OF THE HIGHER SECONDARY SCHOOL STUDENTS TOWARDS POLITICAL SCIENCE: A STUDY IN BAMUTIA R. D. BLOCK - Dey, Pradip (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Political science is a fundamental discipline that introduces students to the principles of governance, political systems, and public policy. At the higher secondary school level, the study of political science holds significant importance in cultivating informed and engaged citizens. Understanding students' attitudes towards political science can provide valuable insights into their interest levels, perception of relevance, and potential engagement with civic issues. Research in this area can help educators tailor their teaching methods to enhance learning experiences and foster active participation in the political process. In the specific context of Bamutia R.D Block, the study was conducted to explore the attitudes of higher secondary school students towards political science to address the gaps in curriculum delivery and student engagement. The study concludes that students have positive attitude towards political science. It indicated that factors such as the provision of instructional materials including computers, provision of appropriate and adequate textbooks for both tutors and students were the top factors that facilitated the teaching and learning of political science concepts. It also came to light that lack of TLMs, lack of libraries and political science resource room which were the top factors which greatly hampered the teaching and learning of political science concepts. The study recommends that schools must conduct field trips and educational tours in every academic year to develop positive attitude among the students towards political science subject.